The prevalence of K-RAS mutation in pancreatic adenocarcinoma at the Johannesburg Academic Hospitals - Ngwenya, Sharol Philile (My University, 2020)
ABSTRACT Introduction: Pancreatic adenocarcinoma (PDAC) is a disease with a high mortality and morbidity worldwide and current treatment options have proven largely ineffective. The tumour has certain well recognised risk factors of which genetic risk factors are critical in the development thereof. KRAS gene is the most commonly mutated gene and is an early event in the carcinogenesis. Materials and Methods: A retrospective study was performed of cases received at Johannesburg Academic Hospitals, to determine the frequency of KRAS mutations in pancreatic adenocarcinoma. SNOMED search from January 2006 and December 2010 revealed 132 cases of PDAC of which 40 randomly selected cases underwent KRAS testing that proved successful in 28 cases. Five 3 μm thick tissue sections of tumour were cut, and subjected to deoxyribonucleic acid (DNA) extraction. The DNA product was amplified for KRAS exon 2 using polymerase chain reaction (PCR) followed by DNA sequencing of the purified PCR amplicons. Results: Of the 28 patients, 11 were female (39.3%) and 17 males (60.7%). The age of the patients ranged from 38 to 78 years with mean of 60.6 years (standard deviation of 9.6). KRAS mutational analysis was performed on forty cases, successful in 28, 19 of which showed KRAS mutations (67.9%). Conclusion: A high frequency of KRAS mutations in PDAC of 67.9% was noted in this study. The key to managing this devastating neoplasm lies in targeted therapies against the KRAS pathway and mutational testing for KRAS in pancreatic adenocarcinoma may become routine in the future
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Medicine (Anatomical Pathology), 2020